The Influence of Empathy Trait and Gender on Empathic Responses. A Study With Dynamic Emotional Stimulus and Eye Movement Recordings - Martínez-Velázquez, Eduardo S.; Ahuatzin González, Alma L.; Chamorro, Yaira; Sequeira, Henrique (Frontiers in Psychology, 2020)
Previous studies have suggested that empathic process involve several components such as cognitive empathy, affective empathy, and prosocial concern. It has also been reported that gender and empathy trait can influence empathic responses such as emotional recognition, which requires an appropriate scanning of faces. However, the degree to which these factors influence the empathic responses, has not yet been specified. Aim: The aim of the present study was to identify the differences between individuals with high and low level of empathy trait, as well as differences between men and women, in an explicit task in order to evaluate the empathic responses. Methods: We recorded eye movements during the presentation of dynamic emotional stimuli (joy, anger, fear and neutral videos). After watching each video, participants had to rate the valence and arousal dimensions of emotional content and explicit empathy responses were assessed. Thirty participants (15 women) were included in a High Empathy group (HE; mean age= 21.0) and 30 participants (16 women) in the Low Empathy group (LE; mean age= 21.2), according to their scores in the Interpersonal Reactivity Index (IRI) scale. Results: The HE group showed higher scores than the LE group in the explicit empathy responses. These differences, based on global scores, were mainly explained by affective empathy and cognitive empathy responses but not by emotional recognition one. No differences were observed by gender in these measures. Regarding eye movements in the dynamic emotional stimuli, HE group had longer fixation duration on the eyes area than LE group. In addition, women spent more time on the eyes area in comparison to men. Discussion: Our findings suggest that both men and women with high empathy trait are more accurate to empathizing but not on the basis of the emotional recognition response. The fact that women spent more time on the eyes area did not seem to affect the empathic responses to the dynamic emotional stimulus. Overall, empathic responses of both men and women are modulated by their empathic trait. In addition, empathic trait and gender seem to impact strategies to deal with emotional facial information.